A noninvasive H. pylori stool antigen assay to detect H. pylori infection of in vivo BALB/c mice models - Wang, Y L; Sheu, B S; Yang, H B; Huang, A H (Hepato-gastroenterology, 2001)
Previous tests for H. pylori infection status of mice have required sacrificing the small host for histological evaluation. We thus aim to determine whether a noninvasive HpSA (H. pylori-specific stool antigen assay) could be applied to detect H. pylori infection in living mice. A total of 60 BALB/c specific pathogen-free mice were used, 20 per control group and 40 per exposed group, the exposed group being challenged with H. pylori isolates. In both groups, the stool samples of each mouse were collected before, 7 days, and 4 weeks after the challenge with H. pylori isolates in the exposed group. All the stool samples were processed with HpSA to detect the presence of H. pylori infection. Four weeks after the inoculation of the exposed group and no inoculation in the control group, each mouse received gastrectomy for histology to judge the presence of H. pylori. None of the mice had a positive histology in the control group. Five BALB/c mice expired due to H. pylori inoculation in the exposed group. Four weeks after inoculation, 85.7% (30/35) of the BALB/c mice achieved the H. pylori infection. Applying the stool samples collected on the 7th day and selecting cutoff point as 0.2, the sensitivity and specificity of HpSA to detect the H. pylori colonization achieved as 100% and 88%, respectively. The 4th week stool samples for HpSA achieved a high sensitivity as 96.6% and specificity as 96% to detect H. pylori infection rate, while choosing cutoff point as 0.20. HpSA can be an effective tool without subject lethality to detect H. pylori infection in BALB/c mice model.